MEWUJUDKAN PERPUSTAKAAN PERGURUAN TINGGI YANG RAMAH DIFABEL - Isrowiyanti, Isrowiyanti (BACA: Jurnal Dokumentasi dan Informasi, 2013)
This study aims to: 1) raise the institutions awareness about disabilities, especially the awareness in the university library that disability is a part of the academic society. The disabled people have the same rights for facilities and learning support services, therefore every university library should be inclusive and can serve user with disabilities; 2) university library should become disabilities-friendly. This study used literature study and also observation and interviews. The result of this study showed the elements which support university library to be disabilities-friendly namely facilities and infrastructure, human resource, and program socialization.